Involuntary backsourcing in the public sector: From conflict to collaboration. (5th May 2021) - Berlin, Johan M.; Jansson, Magnus; Karlsson, David; Carlström, Eric D.
Abstract: The aim of this study is to contribute to the literature on how involuntary backsourcing in public organizations is performed in practice and how it affects the relationship between principal and agent. The study focuses on two questions: (1) Which stages characterize the process when public contracts are involuntary terminated? (2) How does involuntary backsourcing affect the relationship between principal and agent during the transfer period? The study's case concerns public backsourcing in Sweden, in particular, how a metropolitan municipality manages involuntary backsourcing. This study provides in‐depth insights into backsourcing and its practice, as well as the degree to which the conflict dimension between the parties is affected. The study shows—paradoxically—that the relationship between principal and agent during the transition phase is characterized by dependence, mutual exchange of information, collaboration, and less conflict. The study contributes to developing the theory of backsourcing, particularly the behavior that is played out between principal and agent in the transition stage. The findings identify the need for public organizations which make outsourcing decisions to have contingency plans for bringing operations back in‐house.